Association between White Coat Hypertension and Left Ventricular Hypertrophy among Adult Nigerians. (African Journal of Biomedical Research, 2021)
Background: There has been an age-long controversy on whether white coat hypertension (WCH) is associated with end organ damage or not. Hence, the presence of left ventricular hypertrophy was assessed in individuals with WCH. This study determined the association between WCH and left ventricular hypertrophy among adult Nigerians.Patients and Methods: A total of 88 participants consisting of 44 patients with WCH and 44 age and sex-matched normotensive controls were studied. They all underwent 24-hour ambulatory blood pressure assessment and echocardiography.Results : Thirty one (70.5%) females were in each group. The mean body mass index of patients (26.4 ± 4.5kg/m2) was significantly higher than that of the controls (23.8 ± 4.3kg/m2). Twenty-four (54.5%) of 44 patients and 19 (43.2%) of 44 controls had left ventricular hypertrophy; (chi square=1.137, p-value=0.286).Conclusion: WCH and normotension have similar risk of left ventricular hypertrophy among adult Nigerians. The data reviewed in this paper underscore the importance of assessing the presence of target organ damage in both white-coat hypertension and normotension in the Nigerian population. In Nigeria, there is currently no study linking WCH and left ventricular hypertrophy. Hence, more studies are necessary to assess the presence of left ventricular hypertrophy in these categories of individuals.